Influence of Media Credibility and Information Quality on Visiting Interest: An Analysis of the @WonderfulIndonesia Instagram Account on Millennial Travelers - Purwitasari, Endah; Farida, Nuke; Wijaya, Widiastiana Vista; Wulandari, Christiana (CHANNEL: Jurnal Komunikasi, 2024)
Tourism in Indonesia holds significant potential, with domestic tourism being a primary focus for the government. The Ministry of Tourism and Creative Economy of the Republic of Indonesia has developed the "Wonderful Indonesia" branding, utilizing the @WonderfulIndonesia Instagram account to promote domestic tourism. This study examines the impact of media credibility and information quality on millennials' interest in visiting domestic tourist destinations, using the @WonderfulIndonesia account as a case study. Utilizing the Elaboration Likelihood Model (ELM) theory, the research emphasizes the importance of persuasive message delivery through digital platforms. Data were collected from a survey of 30 respondents and analyzed using validity, reliability, and multiple regression tests with SPSS 26. Results indicate that media credibility and information quality account for 31.6% of the variance in visiting interest, demonstrating a significant positive relationship. However, 69.4% of the variance is influenced by other factors, suggesting the need for further research into variables such as media exposure and content attractiveness.